Empowering women to persevere in confronting violent extremism in communities - Asst.Prof.D. Sadda, Ali Hadi Hadi; Ali, D. Jamal Fatah Ali (Sulaimani Journal for Humanities, 2025)
Human behaviors throughout the ages have mostly been based on the justice of heaven and have inflicted a lot of injustice on their societies. The most horrific injustice is the oppression of women’s rights, despite all the tremendous progress that man has achieved in the modern era and the era of globalization. The importance of the research is crystallized in shedding light on the phenomenon of violent extremism and the violence against women it causes in an analytical attempt to clarify the motives, outcomes and possible treatments for this phenomenon. The research was divided into, the introduction, the first requirement: defining the concept of violence and the concept of extremism, and the second requirement: The intellectual building to confront extremism, the third requirement is protection from extremism and deviation, the fourth requirement is “the danger of women being influenced by violent extremism, and the fifth requirement is “methods of preventing and treating women from being influenced by violent extremism. According to the study, some results and proposals were developed to prevent the escalation of violence, increase its rate, and reduce its severity in societies.
Keywords: Empowerment; women; violence; intellectual extremism